Optimization of Inhibitory Effects of Thymus daenensis Celak and Zataria multifera Boiss Essential Oils on Candida albicans Using Response Surface Methodology and Artificial Neural Network: Inhibitory Effects of Thymus daenensis Celak and Zataria multifera Boiss Essential Oils o n Candida albicans - Sanei, Seyed Javad; Ahmad Khan, Mohd Sajjad (Iranian Journal of Pharmaceutical Sciences, 2019)
Fungus Candida albicans has received much attention due to its oral, vaginal and/or systemic candidiasis.This study was undertaken to find out the optimum concentration of two essential oils of Thymus daenensis Celak. and Zataria multiflora Boiss that have been effective on the C. albicans. The essential oils (EOs) were obtained by hydrodistillation method from T. daenensis and Z. multifera and Time-dependent killing potential of essential oils were assessed in phosphate buffered saline solution containing the desired concentrations of the test agents and yeast suspension. Time of action, concentration of individual or EO mixture and T. daenensis:Z.multifera mass ratio predicted using response surface methodology (RSM) and artificial neural network (ANN).RSM and ANN techniques predicted the 0.8% as an optimum percentage concentration of EO mixture in oils ratio T. daenensis:Z. multifera 1:1, ensuring the highest antifungal effect of 95.8% and 96.4% after 20 h.Appraisal of the models through the coefficient of determination (R2) and mean-square error (MSE) show that the ANN was superior (R2= 0.994) to the RSM model (R2= 0.957) in predicting the percentage of reduced cells.Our data confirmed that proper EOs mixtures may reduce the minimum effective dose of individual EOs.